Pervasive tree-growth reduction in Tibetan juniper forests - Mu, Yu-Mei; Zhang, Qi-Bin; Fang, Ouya; Lyu, Lixin; Cherubini, Paolo (Forest ecology and management, 2021)
•Past tree-growth reductions were identified from sustained narrow ring widths.•Growth reduction occurred intermittently in Tibetan juniper forests in the past.•Synchronized tree-growth reduction reflected episodes of decreased forest health. Recent forest declines have been reported at many sites across the world and attributed largely to global-warming induced droughts. Occurrence of forest declines before the global warming is not well understood, especially with regard to its long-term characteristics. Here, we use tree-ring data to detect periods of growth reduction in 1429 juniper trees from 48 sites on the Tibetan Plateau (TP). We find that tree-growth reduction has occurred intermittently and dispersedly over the TP in the past 350 years. The growth reductions among trees could be synchronized at site level in different time, reflecting episodes of decreased forest health. Tree-growth reduction has been alleviated since the 1980s; sites that do show growth reduction events in recent decades are located at higher elevations and are more sensitive to winter mean temperature. We conclude that the pervasive tree-growth reductions may be related to irregular natural disturbances than climatic anomalies. The state of forest health can be estimated by identifying episodes of synchronous tree-growth reduction. Our findings help account for historical growth reduction in the assessment of forest health risks under future climate change.